Upaya Penanaman Nilai-Nilai Pendidikan Karakter bagi Peserta didik melalui Kegiatan Keagamaan di SMK Assa’adah Bungah - Fahimatul Anis; Adrijanti Adrijanti (Paradigma: Jurnal Filsafat, Sains, Teknologi, dan Sosial Budaya, 2022)
This study aims to find out and explain how the implementation of character education through student religious activities at SMK Assa'adah Bungah. This study used a qualitative approach and a descriptive method with a case study research design. Data collection techniques using observation, interviews, and documentation studies. The subjects of the study include principals, teachers, students. Meanwhile, data analysis is carried out by condensing data, presenting data, and verifying data. To test the validity of the data by using credibility, transferability. The research stages include: pre-field stage, entering the field, data analysis, and writing stage. The results of this study show that efforts to instill the value of character education in students through religious activities carried out at SMK Assa'adah Bungah through several activities including: Tahfidz Program, Tartilul Qur’an Guidance(BTQ), Dhuha Prayer and istighosah around. The result of instilling the value of character education is honesty, discipline, social care and environmental care. Conclusion The planting of the value of character education at SMK Assa'adah Bungah was carried out well because there was good planning and communication between teachers and students as well as the role of parents.